Low-metallicity Galaxies from the Dark Energy Survey - Yu-Heng Lin; Claudia Scarlata; Vihang Mehta; Evan Skillman; Matthew Hayes; Kristen B. W. McQuinn; Lucy Fortson; Katherine Chworowsky; Leonardo Clarke (The Astrophysical Journal, 2023)
We present a new selection of 358 blue compact dwarf galaxies (BCDs) from 5000 square degrees in the Dark Energy Survey, and the spectroscopic follow-up of a subsample of 68 objects. For the subsample of 34 objects with deep spectra, we measure the metallicity via the direct T _e method using the auroral [O iii ] λ 4363 emission line. These BCDs have an average oxygen abundance of 12+log(O/H) = 7.8, with stellar masses between 10 ^7 and 10 ^8 M _⊙ and specific star-formation rates between ∼10 ^−9 and 10 ^−7 yr ^−1 . We compare the position of our BCDs with the mass–metallicity ( M – Z ) and luminosity–metallicity ( L – Z ) relation derived from the Local Volume Legacy sample. We find the scatter about the M – Z relation is smaller than the scatter about the L – Z relation. We identify a correlation between the offsets from the M – Z and L – Z relation that we suggest is due to the contribution of metal-poor inflows. Finally, we explore the validity of the mass–metallicity–SFR fundamental plane in the mass range probed by our galaxies. We find that BCDs with stellar masses smaller than 10 ^8 M _⊙ do not follow the extrapolation of the fundamental plane. This result suggests that mechanisms other than the balance between inflows and outflows may be at play in regulating the position of low-mass galaxies in the M – Z –SFR space.